Gene Therapy Leaves a Vicious Cycle - Goswami, Reena; Subramanian, Gayatri; Silayeva, Liliya; Newkirk, Isabelle; Doctor, Deborah; Chawla, Karan; Chattopadhyay, Saurabh; Chandra, Dhyan; Chilukuri, Nageswararao; Betapudi, Venkaiah (Frontiers in Oncology, 2019)
The human genetic code is the vehicle that drives the synthesis of proteins necessary for life-sustaining biological processes. Though the genetic ciphering remains unchanged through generations, some genes get disrupted, deleted and/or mutated, manifested as diseases and disorders. Current treatment options—chemotherapy, protein therapy, radiotherapy, and surgery available for less than 500 diseases—neither cure nor prevent genetic errors, but rather, often cause many side effects. However, gene therapy, colloquially called “living drug,” provides a one-time treatment option by rewriting or fixing errors in the natural genetic ciphering. Since gene therapy is predominantly a viral vector-based medicine, it has met with a fair bit of skepticism from both the science fraternity and patients. Now, thanks to advancements in gene editing and recombinant viral vector development, the interest of clinicians and pharmaceutical industries has been rekindled. With the advent of more than 12 different gene therapy drugs for curing cancer, blindness, immune, and neuronal disorders, this emerging experimental medical treatment has yet again come in the limelight. The present review article delves into the popular viral vectors used in gene therapy, advances, challenges, and perspectives.